The Effect of Audit Quality and Accounting Conservatism on Tax Avoidance in Companies That Are Members of The Sri Kehati Index - Rizkiana Rizkiana; Suripto Suripto (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
The phenomenon that has occurred in tax avoidance by PT. Toyota Motor Manufacturing Indonesia by utilizing transfer pricing transactions to avoid paying taxes. This is done to avoid paying high taxes in Indonesia. This study aims to provide empirical evidence of the effect of audit quality and accounting conservatism on tax avoidance. This study uses a quantitative approach and the data used are secondary data in the form of annual reports and annual financial reports. The population in this study are companies that are members of the Sri Kehati index which are listed on the Indonesia Stock Exchange for the 2016-2020 period. Determination of observation data using purposive sampling in order to obtain observation data as many as 20 companies with a total research observation data is 100 observation data. The data analysis technique used in this study is panel data regression with several tests including descriptive statistical tests, panel data model tests, panel data model selection tests, classical assumption tests, panel data regression tests, coefficient of determination test (R2), F test (simultaneous test), and t test (partial test) with the help of statistical data processing software E-views version 9. The results showed that audit quality had an effect on tax avoidance. Accounting conservatism has no effect on tax avoidance. Audit quality and accounting conservatism have an effect on tax avoidance.